Generated Sets of the Complete Semigroup Binary Relations Defined by Semilattices of the Class ∑(6)(X,5) - Tsinaridze, Nino; Tavdgiridze, Giuli; Givradze, Omar (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
In this article, we study generated sets of the complete semigroups binary relations defined by semilattices unions of the class ∑(6)(X,5)